Valuation of Rice Farmers’ Preferences and Willingness to Pay for Climate-Smart Agricultural Technologies in Southeast, Nigeria - Olive, Osuafor Ogonna; David, Ude Kingsley (Asian Journal of Economic Modelling, 2021)
This paper sought to investigate the valuation of rice farmers’ preferences and willingness to pay for climate-smart agricultural technologies in Southeast Nigeria. Two objectives and one hypothesis guided the conduct of the study. The examination of rice farmers’ willingness-To-Pay (WTP) for improved CSA technology services revealed greater proportion of the respondents to be strongly not willing to pay for over 77.8% of the CSA technologies while barely 7.4% were mildly willing to pay. Rice farmers were strongly not willing to pay for the following CSA technologies: rainwater harvesting, cover crops method, directed seeded rice, systems of rice intensification, use of solar pumps, etc, while the CSA technologies they were mildly willing to pay for are drip irrigation and drainage management. The major reason for respondent’s unwillingness to pay were: poverty (2.0%) and CSA technologies as the responsibility of the Government to farmers within the state (5.0%). For the estimated willingness to pay value, the mean monthly minimum WTP in South-East was estimated at ₦5176.7123 while the mean monthly maximum WTP for rice farmers was estimated as ₦10,926.95. Water-smart technologies (76.8%) was mostly preferred CSA technology. Based on the ordered probit regression analysis of factors influencing willingness to pay for CSA technology, primary occupation (X5), access to credit (X8) and distance to market (X12) were found to be significant. The study recommended that rice farmers should adapt to climate change, natural resource pressure and contribute to mitigating climate change.